Terjemahan Kitab al-Luma‘ dan Analisis Perbahasan Ru’yah Allah Menurut al-Ash‘ari: Translation of al-Luma‘ and Discussion of Ru’yah Allah According to al-Ash‘ari - Kamarzaman, Mohd Haidhar; Azmi, Mohd Faizul; Mahmood, Abdull Rahman; Stapa, Zakaria; Wan Zakaria, Wan Fariza Alyati; Ismail, Indriaty (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The debate about the ru’yah Allah was started by Mu’tazilites as early as 100 Hijri. They deny that Allah can be seen by the Mu’min in the hereafter with the argument of tanzih mutlaq. Al-Ash‘arī, who was born around the third century of Hijri, debated this issue according to the framework of Ahl al-Sunnah wa al-Jama‘ah. He wrote a book named al-Luma‘ and discussed the specific issue of the ru’yah Allah aimed to counter-argue the Mu’tazilites’s understanding. This study analyzes the debate of ru’yah Allah presented by Muslim scholars in general and al-Asha‘rī in particular. This study aims to highlight the importance of ru’yah Allah’s discussion in Kalām discourse and to provide understanding into this issue according to al-Ash‘arī’s perspective through the translation of his great work in the debate on ru’yah Allah’s. This study uses comparative analysis methods, historical based analysis as well as inductive and deductive text analysis. The study found that the ru’yah Allah was an important issue in the debate on Kalām because almost all scholars of the time, salaf or khalaf discussed this issue in their books. The study also found that al-Ash‘arī had successfully solved the entire problem of ru’yah Allah in al-Luma‘ in order to provide understanding to the public in eradicating the teachings of Mu’tazilites.